Vegetarian cooking around the world - Behnke, Alison (Minneapolis, MN : Lerner, 2002)
Includes recipes for meatless soups, salads, main dishes, and side dishes, expanded material on healthy and low-fat cooking and vegetarian nutrition, and an expanded cultural section on holidays and festivals.
"Revised and expanded to include new low-fat and vegetarian recipes."
Includes index.
5.5
5-8
Keywords: Vegetarian cooking; International cooking